2005
DOI: 10.1529/biophysj.104.056192
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Dictates the Freedom of EGF Receptors and HER2 in the Plane of the Membrane

Abstract: The flow of information through the epidermal growth factor receptor (EGFR) is shaped by molecular interactions in the plasma membrane. The EGFR is associated with lipid rafts, but their role in modulating receptor mobility and subsequent interactions is unclear. To investigate the role of nanoscale rafts in EGFR dynamics, we used single-molecule fluorescence imaging to track individual receptors and their dimerization partner, human epidermal growth factor receptor 2 (HER2), in the membrane of human mammary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
112
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 85 publications
(120 reference statements)
11
112
1
Order By: Relevance
“…The single-molecule fluorescence technique was described earlier in detail. 43 Briefly, three criteria were used to identify individual fluorophores. (1) The size of the fluorescent spot should www.acsnano.org be at the diffraction limit, which is about half of the excitation wavelength, or 3ϫ3 pixels (300 nm 2 ), under our experimental conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The single-molecule fluorescence technique was described earlier in detail. 43 Briefly, three criteria were used to identify individual fluorophores. (1) The size of the fluorescent spot should www.acsnano.org be at the diffraction limit, which is about half of the excitation wavelength, or 3ϫ3 pixels (300 nm 2 ), under our experimental conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental and theoretical investigation of EGF binding [3,9,17] emphasized the importance of spatial distribution of receptors. Ample experimental evidence indicates that EGF receptors can have a highly inhomogeneous distribution characterized by small areas of high density [30], and exhibit anomalous diffusion [20]. There are other examples of receptors that exhibit clustering and anomalous diffusion [1].…”
Section: The Microscopic Picturementioning
confidence: 99%
“…The current picture [28] is more structured, with microdomains of lipids and proteins [6,13,24]. Modern microscopy techniques [22,29] provide direct evidence of the effect of these structures on membrane receptor localization and movement [1,18,20], revealing receptor clusters in static images, and intervals of confinement in small areas separated by jumps or "hops" in single particle tracking.…”
Section: Introductionmentioning
confidence: 99%
“…Many single molecule studies on signaling receptors have offered new insights into their localization, assembly, and activation during the singal transduction process. [18][19][20][21][22][23][24][25][26] In these studies, a decrease in receptor lateral mobility after receptor activation is usually observed. For example, single-molecule imaging of small G protein Ras revealed that Ras diffusion slowed down on activation.…”
Section: Introductionmentioning
confidence: 99%